TECHNOLOGY FOR DEVELOPING CRITICAL THINKING IN MEDICAL EDUCATION STUDENTS THROUGH MODELLING BIOLOGICAL PROBLEMS - Sanjarbek Atakhanov Anvarovich; Rukhshona Abdumannobova; Akmaljon Bahodirov Jahongirovich (TADQIQOTLAR, 2025)
Abstract:  The  article  highlights  the  essence,  methods,  and  significance  of developing  critical thinking  skills in  medical education students through biological problem modelling technologies. The types of biological modelling technologies, their integration into the educational process, and their role in shaping critical thinking are analyzed on a scientific basis. The practical significance of modelling in enhancing students' analytical and research skills is demonstrated through examples. Additionally, the article discusses the prospects of biological modelling in medical education and the opportunities for improving educational quality with the help of modern technologies.